2017
DOI: 10.1186/s13018-017-0563-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of 167 consecutive cases of acetabular fractures using the Kocher-Langenbeck approach: a case series

Abstract: BackgroundAcetabular fractures are quite challenging injuries for the orthopedic surgeon because of their low incidence and their deep and complex anatomy. The objective of this study was to evaluate surgeon-independent parameters that might influence radiographic outcome and early complication rates of high-energy acetabular fractures treated by open reduction and internal fixation via the Kocher-Langenbeck approach, the golden standard for posterior access.MethodsOne hundred sixty-seven consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
3
21
3
11
Order By: Relevance
“…Post-traumatic osteoarthritis is the most common complication of femoral head fracture, and its incidence is directly related to the quality of fracture reduction. 32 , 33 , 35 In our study, three patients developed post-traumatic osteoarthritis, resulting in a lower incidence than the 21.6% reported in the literature. 33 …”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Post-traumatic osteoarthritis is the most common complication of femoral head fracture, and its incidence is directly related to the quality of fracture reduction. 32 , 33 , 35 In our study, three patients developed post-traumatic osteoarthritis, resulting in a lower incidence than the 21.6% reported in the literature. 33 …”
Section: Discussioncontrasting
confidence: 48%
“…Lukas et al. 33 drew a similar conclusion. After anatomic reduction has been achieved, internal fixation should be performed.…”
Section: Discussionmentioning
confidence: 75%
“…As mentioned by Matta et al, [24] the main complication following a fracture of the acetabulum is post-traumatic osteoarthritis. The incidence of osteoarthritis in our series was 60.8%, which is considerably higher than that reported by Isaacson et al, [30] 52% and the 21.6% reported by Negrin et al, [31]. Iatrogenic nerve injury included sciatic nerve, femoral nerve and lateral cutaneous nerve of thigh are possible complication during acetabular surgery.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study, the mean interval between injury and the surgical procedure was found to be 3.2 days with a mean surgical time of 79.8 minutes, and blood loss of 179.15cc. The time of surgery and amount of bleeding are lower than the average of the standard and modified approaches specified in the literature, in particular (Negrin, 2017). Complications such as DVT and PE, which were reported as 8% in the literature, were not detected in any of our cases (Negrin, 2017).…”
Section: Discussionmentioning
confidence: 49%
“…The time of surgery and amount of bleeding are lower than the average of the standard and modified approaches specified in the literature, in particular (Negrin, 2017). Complications such as DVT and PE, which were reported as 8% in the literature, were not detected in any of our cases (Negrin, 2017). In 2 patients, superficial wound infections were observed and the mean duration of surgery and total blood loss were up to the average (Magu,2011).…”
Section: Discussionmentioning
confidence: 58%